Conducting Polymer‐Ionic Liquid Electrode Arrays for High‐Density Surface Electromyography. Issue 17 (14th May 2021) - Velasco‐Bosom, Santiago; Karam, Nuzli; Carnicer‐Lombarte, Alejandro; Gurke, Johannes; Casado, Nerea; Tomé, Liliana C.; Mecerreyes, David; Malliaras, George G.
Abstract: Surface electromyography (EMG) is used as a medical diagnostic and to control prosthetic limbs. Electrode arrays that provide large‐area, high density recordings have the potential to yield significant improvements in both fronts, but the need remains largely unfulfilled. Here, digital fabrication techniques are used to make scalable electrode arrays that capture EMG signals with mm spatial resolution. Using electrodes made of poly(3, 4‐ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) composites with the biocompatible ionic liquid (IL) cholinium lactate, the arrays enable high quality spatiotemporal recordings from the forearm of volunteers. These recordings allow to identify the motions of the index, little, and middle fingers, and to directly visualize the propagation of polarization/depolarization waves in the underlying muscles. This work paves the way for scalable fabrication of cutaneous electrophysiology arrays for personalized medicine and highly articulate prostheses. Abstract : The development of easy to fabricate and customize cutaneous electrophysiology electrode arrays for high spatial resolution recordings is reported. Their mechanical flexibility and non‐drying electrodes allow the acquisition of high‐quality signals. These devices have the potential to enable personalized medicine and highly articulated myoelectric prostheses.